Agricultural breadbaskets shift poleward given adaptive farmer behavior under climate change. (7th October 2021) - Franke, James A.; Müller, Christoph; Minoli, Sara; Elliott, Joshua; Folberth, Christian; Gardner, Charles; Hank, Tobias; Izaurralde, Roberto Cesar; Jägermeyr, Jonas; Jones, Curtis D.; Liu, Wenfeng; Olin, Stefan; et al.
Abstract: Modern food production is spatially concentrated in global "breadbaskets." A major unresolved question is whether these peak production regions will shift poleward as the climate warms, allowing some recovery of potential climate‐related losses. While agricultural impacts studies to date have focused on currently cultivated land, the Global Gridded Crop Model Intercomparison Project (GGCMI) Phase 2 experiment allows us to assess changes in both yields and the location of peak productivity regions under warming. We examine crop responses under projected end of century warming using seven process‐based models simulating five major crops (maize, rice, soybeans, and spring and winter wheat) with a variety of adaptation strategies. We find that in no‐adaptation cases, when planting date and cultivar choices are held fixed, regions of peak production remain stationary and yield losses can be severe, since growing seasons contract strongly with warming. When adaptations in management practices are allowed (cultivars that retain growing season length under warming and modified planting dates), peak productivity zones shift poleward and yield losses are largely recovered. While most growing‐zone shifts are ultimately limited by geography, breadbaskets studied here move poleward over 600 km on average by end of the century under RCP 8.5. These results suggest that agricultural impacts assessments can be strongly biased if restricted in spatial area or in the scope of adaptive behavior considered. Accurate evaluation of food security under climate change requires global modeling and careful treatment of adaptation strategies. Abstract : A major unresolved question in climate impacts on agriculture is whether regions of peak production will shift poleward as the climate warms, allowing some recovery of potential climate‐related losses. We employ an ensemble of process‐based global crop models under the Gridded Crop Model Intercomparison Project (GGCMI) and find that regions of peak yield for rice, maize, soybean, and wheat move poleward if growing seasons are allowed to adapt with climate change. However, adaptation by shifting cultivation is ultimately limited by geography in many regions.